Multivariate Modeling in Quality Control of Viscosity in Fuel: An Application in Oil Industry - Freitas, Leandro Valim de; Marins, Fernando Augusto Silva; Freitas, Ana Paula Barbosa Rodrigues de; Silva, Messias Borges; Loures, Carla Cristina Almeida (IntechOpen, 2012)
None